1994
DOI: 10.5144/0256-4947.1994.198
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Cystosarcoma Phyllodes: A Review of the Clinical Experience at King Faisal Specialist Hospital and Research Centre

Abstract: Twelve females with cystosarcoma phyllodes of the breast were referred to King Faisal Specialist Hospital and Research Centre (KFSH&RC) between 1980 and 1990, representing 0.8% of breast cancer patients seen during this period. Median age was 45 years (range 16 to 65 years). Seven patients (58%) were premenopausal. All patients presented with breast mass, which measured >10 cm in 58% of them. The median duration of symptoms was 15 months (range two to 174). Neither axillary lymph nodes nor distant metastases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Throughout the years, the reported incidence of PT in all its forms remains to be <1%, with a mean age of occurrence ranging from 35-55 [1,2]. These tumors are more common to occur in women than men, with reported a correlation between multiparity and the incidence of PT [6,7], yet there are also reported cases in pediatric patients [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the years, the reported incidence of PT in all its forms remains to be <1%, with a mean age of occurrence ranging from 35-55 [1,2]. These tumors are more common to occur in women than men, with reported a correlation between multiparity and the incidence of PT [6,7], yet there are also reported cases in pediatric patients [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the usually large size of PT, skin ulceration could occur; yet it does not pertain to being a sign of malignancy [13]. The same goes for axillary lymph node enlargement, which occurs due to the presence of infections and necrosis accompanying the mass [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best predictor of the prognosis for BC depends on the histological grade that includes the morphological assessment of tumor biological characteristics [7,8]. In Riyadh, a study that took place between 1980 and 1990 reported that in 58% of cases the mass was greater than 10 cm, and there were no axillary lymph nodes or metastases found during examination [9]. Another study in the same period (1975 to 1991) reported that 64% of BC cases were diagnosed in advanced or metastatic stages (III & IV) [10].…”
Section: Introductionmentioning
confidence: 99%